Microstructure and Texture of Ni7W/Ni12W/Ni7W Composite Substrates at Different Intermediate Annealing Temperatures. Issue 10 (October 2018) - Jing, Liu; Hongli, Suo; Lin, Ma; Dan, Yu; Jin, Cui; Yaotang, Ji
Abstract: Ni7W/Ni12W/Ni7W composite substrates for YBa2 Cu3 O7-δ coated conductors were prepared by rolling assisted biaxially textured substrates route. A threefold intermediate annealing at different temperatures was introduced in the rolling process of Ni7W/Ni12W/Ni7W composite substrates to optimize the deformation texture. The recovery microstructure and the deformation texture of latitude and longitude section were studied with X-ray diffraction and electron backscattered diffraction to reveal the possible mechanism of temperature effects on rolling and strong cube texture formation processes. The results show that the highest cube area fraction is found in sample intermediately annealed at 600 °C/60 min; in this way Ni7W/Ni12W/Ni7W composite substrates with high cube texture content of 95% (<10°) are obtained at a low recrystallization annealing temperature. Crystal orientation maps reveal that a higher amount of cube orientation exists in its recovery and initial recrystallization samples. Point to point misorientation files confirm the high grain boundary angle of these cube grains, which strongly boost the cube texture formation during subsequent recrystallization.